Project OPUS: Development and Evaluation of an Electronic Platform for Pain Management Education of Medical Undergraduates in Resource-Limited Settings - Onyeka, Tonia C.; Iloanusi, Nneka; Namisango, Eve; Nagoma, Abubakar U. (PloS one, 2020)
Pain is a very frequent symptom that is reported by patients when they present to health pro fessionals but remains undertreated or untreated, particularly in low-resource settings including Nigeria. Lack of training in pain management remains the most significant obstacle to pain treatment alongside an inadequate emphasis on pain education in undergraduate medical curricula, negatively impacting on subsequent care of patients. This study aimed to determine the effect of a 12-week structured e-Learning course on the knowledge of pain management among Nigerian undergraduate medical students